On Universal Interdependence as the Fourth Law of Dialectics - Mena Ortiz, Juan Diego (2025)
Stalin (1938) posits four principal features of the marxist dialectical method (characterized, following marxist doctrine, as opposing metaphysics). The first of these is what Lefebvre later called Universal Interdependence, which he defined as a dialectical law. At any rate, Universal Interdependence is not unproblematic as it is considered a) the most general of the dialectical laws, b) an opposite of a metaphysical premise and c) ambiguous. This paper aims to overcome these difficulties. The upshot of our solution is that Universal Interdependence ought to be understood as a marxist version of the causal field in the sense of Mackie (1965).